An Education Program to Improve Health Insurance Literacy with Allianz Life Indonesia for PKK Mothers in Pondok Aren, South Tangerang - Ossi Ferli; Deni Wardani; Rizki Khairani Hasibuan; Aradea Margareta; Ratu Aribah Santika Xaviera; Ahmad Devani Yuslah (I-Com: Indonesian Community Journal, 2026)
Health insurance literacy in Indonesia remains low, with a literacy index of 45.45% and an inclusion index of only 28.50% based on the 2025 National Financial Literacy and Inclusion Survey. This gap indicates that understanding has not translated into actual product use, especially among household financial managers. This community service aimed to improve health insurance literacy among PKK mothers in Pondok Aren, South Tangerang, in collaboration with Allianz Life Indonesia. Educational sessions by Allianz VIP Planners covered financial planning, health risk management, and insurance product selection. Pre-test and post-test instruments measured changes in participants' understanding. The activity was attended by 60 participants, exceeding the 30-person target. Results showed 100% of participants improved their understanding, surpassing the 80% improvement target. These findings confirm that community-based education effectively enhances financial literacy and promotes insurance inclusion among household managers.